Produksi DAG Dari Virgin Coconut Oil (VCO) Melalui Reaksi Trans-Esterifikasi Menggunakan Enzim Lipase Dedak Padi (Oryza Sativa L.) Spesifik C18-20 Terimobilisasi Karbon Aktif Sebagai Biokatalis - Dali, Seniwati; Firdaus, Firdaus; Rusman, Hendra J. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2017)
This research aims to produce DAG of the VCO through the substrate reaction of trans-esterification using lipase enzymes specifically C18-20 from rice bran (Oryza Sativa L.) immobiled of activated carbon as a catalyst. Phases of this research starts with the enzyme lipase do immobile using activated carbon; next enzymes of immobile used to produce DAG through the trans-esterification reaction using a VCO as a substrate and methanol as ko-substrate; DAG and methyl ester produced identified using FTIR instrument and GC-MS instruments. The results showed that there were three compounds DAG and three compound methyl ester produced trans-esterification reaction, namely (1) 1-laurin, 3-heksanoin esters of glycerol; (2) 2-laurin, 3-oktanoin esters of glycerol; (3) 1-laurin, 3-heksanoin esters of glycerol; (4) methyl ester oleic; (5) methyl ester stearic acids; and (6) methyl ester arachidat.